Answer:
[tex]x = 2[/tex] ± [tex]\sqrt{7}[/tex]
Step-by-step explanation:
Lets see the quadratic equation :
x = -b ± [tex]\sqrt{b^2 - 4ac}[/tex] / 2a
So now we have our quadratic :
[tex]x^2 - 4x - 3 =0[/tex]
a = ?^2 (Exponent)
b = ?x (Variable)
c = ? (Constant)
So replace every variable in the quadratic equation with the ones in the quadratic formula.
x = -(-4) ± (-4)^2 - 4(1)(-3) / 2(1)
(Imagine (-4)^2 - 4(1)(-3) in a square root)
x = 4 ± [tex]\sqrt{16 - - 12}[/tex] / 2
x = 4 ± [tex]\sqrt{28}[/tex] / 2
Of course 28 isn't available for a square root property, so lets break it up :
x = 4 ± [tex]2\sqrt{7}[/tex] / 2
Simplify the radical :
[tex]x = 2[/tex] ± [tex]\sqrt{7}[/tex]
^^^